1997
DOI: 10.1111/j.1365-3164.1997.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cutaneous T‐cell lymphoma with dacarbazine in a dog

Abstract: Epitheliotropic cutaneous T-cell lymphoma in a Lhasa Apso dog treated with dacarbazine is reported. Clinical disease consisted of a 4 x 4-cm ulcerated mass over the mandibular symphysis and bilateral lymphadenopathy of the submandibular lymph nodes. Skin biopsy sections were diagnostic for epitheliotropic cutaneous T-cell lymphoma, and immunohistochemistry staining for the CD3 antigen was positive. Tissue samples were submitted for chemosensitivity testing and dacarbazine was shown to be 60% effective. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…A case report published in 1996 reported the efficacy of single‐agent DTIC as treatment for cutaneous lymphoma in 1 dog. The dog received 2 cycles of DTIC and remained disease free 1 year after treatment 21 …”
mentioning
confidence: 99%
“…A case report published in 1996 reported the efficacy of single‐agent DTIC as treatment for cutaneous lymphoma in 1 dog. The dog received 2 cycles of DTIC and remained disease free 1 year after treatment 21 …”
mentioning
confidence: 99%
“…There have been few controlled studies to evaluate the response of canine lymphoma to DTIC. A dog with cutaneous lymphoma and nodal involvement achieved a durable complete remission when treated with DTIC 13 . In 2 studies of dogs with relapsed lymphoma, complete and partial remissions were observed when DTIC was combined with doxorubicin 14,15 …”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Therapeutic approaches have been described in the veterinary literature but a standard of care therapy has not been established for canine ELSA. 5,[15][16][17][18] Reported response rates to retinoids, 16 cyclosporine, 18 fatty acids, 5 Lasparaginase, 6 dacarbazine, 15 and pegylated doxorubicin 7 generally are ,50% and are of short duration. A recent publication evaluating 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) in the treatment of ELSA by Williams et al 19 documented an overall response rate of 78%.…”
mentioning
confidence: 99%